Resumo escolar no ensino médio técnico integrado integral: uma experiência de leitura e escrita em uma abordagem sócio-retórica - Souza, Rita Rodrigues de [UNESP] (2015)
This dissertation presents the findings relating to a research about the experience of reading and writing school summaries in the context of Professional Education Middle Level Technical. Was conducted this research with students of the 2nd series of the Integrated Technical Course in Electrical Integral, of one of the campuses of the Federal Institute of Goiás, in 2014. The reading and writing experience aimed at instrumentation and critical awareness of genre, as proposed Aranha (2002, 2004, 2009) and Devitt (2004, 2009). The research presents a nature of qualitative-interpretative ethnographic basis, in accordance with Zaharlick and Green (1991), Serrano (1994), Flick (2009) and Bortoni-Ricardo (2008). In support of read and write experience, was selected, in the light of the socio-rhetorical approach, a theoretical framework relating to key concepts of genre studies. First, was approached the concept of genre from Swales (1990, 1992, 2004, 2009a, 2009b), Dean (2008) and Devitt (1993, 2004, 2009). Then, were used Biasi-Rodrigues, Hemais and Araújo (2009), Swales (1990, 1992) and Hyland (2004) to present the concept of discourse community. Afterwards, was discussed about the communicative purposes, relying on Askehave and Swales (2001), Swales (1990, 2004), Askehave and Nielsen (2004), Biasi- Rodrigues and Bezerra (2012); and, next, for the concept of tasks and the notion of rhetorical structure, were researched subsidies in Swales (1990). As to the pedagogical application of the concepts, was oriented guidelines in Ramos (2004), Hyland (2004), Aranha (2002, 2009) and Devitt (2004, 2009), which contributed to the proposition of a writing course. And, finally, for the realization of a needs analysis, was used studies by Cintra (1992), Benesch (1996, 2006), Songhori (2008), Passarelli and Cintra (2008). The analysis of data needs, from participants' responses to the questionnaire diagnosis revealed that the participants had ...